Inhibition of soluble epoxide hydrolase attenuates eosinophil recruitment and food allergen-induced gastrointestinal inflammation. Issue 1 (17th January 2018) - Bastan, Idil; Ge, Xiao Na; Dileepan, Mythili; Greenberg, Yana G; Guedes, Alonso G; Hwang, Sung Hee; Hammock, Bruce D; Washabau, Robert J; Rao, Savita P; Sriramarao, P
Abstract: Prevalence of food allergies in the United States is on the rise. Eosinophils are recruited to the intestinal mucosa in substantial numbers in food allergen-driven gastrointestinal (GI) inflammation. Soluble epoxide hydrolase (sEH) is known to play a pro-inflammatory role during inflammation by metabolizing anti-inflammatory epoxyeicosatrienoic acids (EETs) to pro-inflammatory diols. We investigated the role of sEH in a murine model of food allergy and evaluated the potential therapeutic effect of a highly selective sEH inhibitor ( trans -4-4-[3-(4-trifluoromethoxyphenyl)-ureido]-cyclohexyloxy-benzoic acid [ t -TUCB]). Oral exposure of mice on a soy-free diet to soy protein isolate (SPI) induced expression of intestinal sEH, increased circulating total and antigen-specific IgE levels, and caused significant weight loss. Administration of t -TUCB to SPI-challenged mice inhibited IgE levels and prevented SPI-induced weight loss. Additionally, SPI-induced GI inflammation characterized by increased recruitment of eosinophils and mast cells, elevated eotaxin 1 levels, mucus hypersecretion, and decreased epithelial junction protein expression. In t -TUCB-treated mice, eosinophilia, mast cell recruitment, and mucus secretion were significantly lower than in untreated mice and SPI-induced loss of junction protein expression was prevented to variable levels. sEH expression in eosinophils was induced by inflammatory mediators TNF-α and eotaxin-1. Treatment of eosinophils with t -TUCB significantly inhibited eosinophil migration, an effect that was mirrored by treatment with 11, 12-EET, by inhibiting intracellular signaling events such as ERK (1/2) activation and eotaxin-1-induced calcium flux. These studies suggest that sEH induced by soy proteins promotes allergic responses and GI inflammation including eosinophilia and that inhibition of sEH can attenuate these responses. Soy protein-induced soluble epoxide hydrolase promotes allergic responses, gastrointestinal inflammation and eosinophilia; pharmacological inhibition of this enzyme leads to attenuation of these responses.